Ambitious rebels : remaking honor, law, and liberalism in Venezuela, 1780-1850. - Zahler, Reuben, 1968- (University of Arizona Press, 2013)
"By examining everyday life in Venezuela's post-colonial period, Reuben Zahler provides a broad perspective on conditions throughout the Americas and the tension between traditional norms and new liberal standards during Venezuela's transformation from a Spanish colony to a modern republic"--Provided by publisher.